MINAT SEKSUAL PADA WANITA PREMENOPAUSE DI KELURAHAN BANGETAYU WETAN KOTA SEMARANG - Kusumawati, Erna (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
ABSTRACK: SEXUAL INTEREST PREMENOPAUSAL WOMEN IN KELURAHAN BANGETAYU WETAN  KOTA SEMARANG. Pre menopause is the time when the body begins to transition toward menopause, this period is generally the level of production of the hormones estrogen and progesterone fluctuate up and down the irregular. The menstrual cycle can suddenly extends or retracts during pre menopause symptoms complained by many mothers i.e. any discomfort while sexual intercourse, Reduced arousal and sexual response in the frequency of sexual intercourse is diminished, since the libido is decreasing.  To know the description of sexual activity in women Pre menopause in village Bangetayu Wetan Semarang.  Type of analytical research of correlation with survey approach. The population was women pre menopause in village bangetayu wetan semarang as many as 71 people, sample research using the technique of sampling with simple rondom sampling.  These results indicate the majority of sexual frequency mother premenopausal most respondents active number of 37 (52.1%), respondents still have an interest in the relationship sesksual by 43 (60.6%). Spending on beauty care costs largely Rp 100,000. Treatment sexual function performed by 40 (56.3%). There is no correlation between the frequency of coitus with an interest in sexual intercourse (p value 0.419). The average age of respondents 42 years. Education respondents mostly high school (SMA / SMK) 37 (52.1%). Premenopausal mothers work are mostly housewives (IRT) 41 (57.7%). Premenopausal mother's husband work in private sectors 54 (76.1%).  Sexual activity in premenopausal women is active, there is no connection between coitus relationship with sexual interest  Keywords: frequency, interest